Calculation of Interaction between Ferromagnetic Solids Simplified by Symmetry Considerations - Luiz e Castro, Leonardo; da Silva Filho, Olavo Leopoldino; de Amaral e Eloi, Marcos Tiago (Physicae Organum, 2017)
We discuss the integration of magnetic interaction between spheres and other solids. We show how to use tensors and their eigenvalues in that calculation in order to take advantage of symmetry properties to simplify the expressions. The calculation is gradually restricted to more symmetrical structures, until we reach the case of two homogeneously magnetized spheres arbitrarily positioned and oriented. This work may help future calculations of interaction between more complex objects, such as spheres with inhomogeneous magnetization, ellipsoids and partially paramagnetic solids.